Penataran Pendidikan Bahasa Arab di IPT: Upgrading the Arabic Education at Higher Learning Institution - Sahrir, Muhammad Sabri (Journal of Islamic Educational Research, 2021)
The field of Arabic education is one of the most important fields of study in Malaysia from various levels of Diploma, Bachelor, Master until Doctor of Philosophy. Its importance is a crystal-clear evidence as Arabic is being taught at various levels of education from kindergarten, primary, secondary, and university to public or private HEIs. Thus, the chapters in this book were compiled, edited and published by UNISZA Press. It aims at sharing current issues related to Arabic language educators and lecturers in Malaysia. This book contains nine systematic chapters beginning with discussions about teaching materials, teaching and learning methods and assessment of learning outcomes. This should be the focus of all parties in efforts to improve the quality of Arabic Language Education in Malaysia. Chapter 1 entitled Arabic Language Teaching and Learning at Malaysian Higher Education Institutions: Selection of Ethics and Evaluation. The discussion in this chapter focuses on the selection and evaluation of teaching and learning materials in Arabic for educators. This discussion ensures that the materials selected for the use in teaching and learning (TnL) sessions are part and parcel with the teaching objectives to be achieved at the end of the TnL session in general, and at the higher learning institution in particular. The selection also must be systematically and structured to create interest in the students. In addition, this chapter also emphasizes the use of a procedural model ASSURE to assist educators in making and selecting TnL materials.